2020
DOI: 10.1088/2515-7639/ab6fd1
|View full text |Cite
|
Sign up to set email alerts
|

The role of pinhole structures in Mo thin films on multi-layer graphene synthesis

Abstract: In this study, the density and oxygen content of Mo thin films were varied by changing the deposition conditions, in order to understand their influence on the catalytic activity of Mo 2 C for the synthesis of multi-layer graphene (MLG). Structural and morphological analysis of Mo 2 C in relation to its catalytic activity indicate that the density of Mo plays a more critical role on MLG synthesis than the oxygen content. Results show that the pinholes present in relatively low density Mo layers act as catalyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In our earlier work 13 , it is shown that the nucleation and growth (or absence thereof) of MLG on Mo 2 C was strongly related to the presence (or absence) of pinholes in Mo 2 C. From this observation, we hypothesize that the Mo 2 C/SiO 2 interface can play an important, bifunctional, role by catalyzing different reactions for MLG growth. To test our hypothesis, in this section we investigate the role of the Mo 2 C/SiO 2 interface in MLG growth on pinhole-free Mo 2 C.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…In our earlier work 13 , it is shown that the nucleation and growth (or absence thereof) of MLG on Mo 2 C was strongly related to the presence (or absence) of pinholes in Mo 2 C. From this observation, we hypothesize that the Mo 2 C/SiO 2 interface can play an important, bifunctional, role by catalyzing different reactions for MLG growth. To test our hypothesis, in this section we investigate the role of the Mo 2 C/SiO 2 interface in MLG growth on pinhole-free Mo 2 C.…”
Section: Resultsmentioning
confidence: 74%
“…In the first part, the thin film deposition process flow of Mo catalysts on Si/SiO 2 substrates will be given. This process is known to result in pinhole-free Mo 2 C, which does not yield MLG growth upon subsequent CVD processing 13 . In the second part, the deposition/patterning of oxides will be explained in order to create an interface which is expected to play a role in MLG synthesis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations